Digitalisasi Ideologi: Mediatisasi Hegemoni Ritual Rambu Solo di Media Sosial - Handayani, Rivi; Ahimsa-Putra, Heddy Shri; Budiman, Christian (Communicatus: Jurnal Ilmu komunikasi, 2020)
This article argues that the emergence of contents related to the Rambu Solo ritual on social media is a manifestation of the hegemonic ideology that was digitalized by the new generation of Toraja. Using the theoretical framework of mediatization, this article aims to explore how the hegemony of Rambu solo ritual operates in social media context. By using virtual ethnography method, it can be explained that the mediatization of the hegemony of Rambu Solo rituals on social media are basically implying three things; firstly, the narrative about the Rambu Solo ritual on social media has given birth to a new form of interaction and communication in a broader scope; secondly, the narrative of Rambu Solo ritual on social media has made the media as a new domain to find meanings about the Rambu Solo ritual; and third, the narrative of Rambu Solo ritual indicates the accommodation efforts of the Torajanese new generation towards the rules that apply in the context of social media with the general characteristics of user-generated content. The Torajanes new generation has voluntarily "continued" this ritual hegemony.Artikel ini berargumen bahwa kehadiran konten-konten ritual Rambu Solo di media sosial merupakan manifestasi dari ideologi hegemonik yang mengalami digitalisasi oleh generasi baru Toraja. Menggunakan kerangka teori mediatisasi, artikel ini bertujuan untuk mengeksplorasi tentang bagaimana hegemoni ritual Rambu Solo ini beroperasi dalam konteks media sosial. Dengan menggunakan metode etnografi virtual, dapat diuraikan bahwa mediatisasi hegemoni ritual Rambu Solo di media sosial ini telah mengimplikasikan tiga hal; Pertama, narasi tentang ritual Rambu Solo di media sosial telah melahirkan bentuk baru dari interaksi dan komunikasi dengan cakupan yang lebih luas; kedua, narasi ritual Rambu Solo di media sosial telah menjadikan media sebagai ranah baru untuk menemukan makna-makna tentang ritual Rambu Solo; dan ketiga, narasi ritual Rambu Solo mengindikasikan adanya upaya akomodasi yang dilakukan oleh para generasi muda Toraja terhadap aturan-aturan yang berlaku dalam konteks media sosial dengan ciri umum user-generated content. Generasi baru Toraja secara sukarela telah â€œmelanjutkanâ€ hegemoni ritual ini.